Konsep Moderat dalam QS. Al Baqarah: 143 (Perspektif Teori Roland Barthes) - Mustofa, Faiz Wildan; Sofia, Adib (Institut Agama Islam Negeri (IAIN) Curup, 2024)
It has been proven that intolerance incidents colour the history of the Indonesian nation, both in the past and the present. Cases of intolerance usually appear more and more, especially in heated political situations. On one hand, the society has an ideal principle, namely moderation. However, viewing the discussion so far, the principle of moderation is still understood as the middle position. The principle of moderation seems to be a passive attitude without any specific action. The Al-Qur'an explains the principle of moderation with the term ummatan wasathan in Surah Al-Baqarah verse 143. This article attempts to interpret the term by using Roland Barthes' semiotics, which sees this term at the level of language and myth. By interpreting the meaning of ummatan wastan at these two levels, a description of the moderation principle can be seen as not a passive position, but rather an active attitude to act fairly in looking at various things. This attitude is an effort to select something in a balanced and fair manner based on various considerations to achieve harmony in life.